2009
DOI: 10.1002/jcp.21970
|View full text |Cite
|
Sign up to set email alerts
|

2‐methoxyestradiol inhibits atorvastatin‐induced rounding of human vascular smooth muscle cells

Abstract: The cardiovascular benefits of statins, including atorvastatin (ATV), have been reported to be gender-dependent, but the underlying mechanism is unclear. In this study we examine whether estrogen and its metabolite, 2-methoxyestradiol (2ME), affect the rounding response of human vascular smooth muscle cells (SMCs) induced by ATV. Twenty-four hour treatment with ATV (10-100 microM) induced rounding of cultured human SMCs. Addition of 2ME (1-20 microM), but not 17beta-estradiol, for 2 h induced re-spreading of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Importantly, 2‐ME when used at physiological and pharmacological conditions, was potent enough to reverse the migration and proliferation of osteosarcoma cells induced by low concentrations of D‐serine and glycine. The anti‐migrative potential of 2‐ME was previously demonstrated (Wu et al, ; Yin et al, ). Similarly to our study, Yin and colleagues evaluated using wound healing assay that 2‐ME at micromolar concentrations inhibits the migration of human vascular smooth muscle cells (Yin et al, ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Importantly, 2‐ME when used at physiological and pharmacological conditions, was potent enough to reverse the migration and proliferation of osteosarcoma cells induced by low concentrations of D‐serine and glycine. The anti‐migrative potential of 2‐ME was previously demonstrated (Wu et al, ; Yin et al, ). Similarly to our study, Yin and colleagues evaluated using wound healing assay that 2‐ME at micromolar concentrations inhibits the migration of human vascular smooth muscle cells (Yin et al, ).…”
Section: Discussionmentioning
confidence: 78%
“…The anti‐migrative potential of 2‐ME was previously demonstrated (Wu et al, ; Yin et al, ). Similarly to our study, Yin and colleagues evaluated using wound healing assay that 2‐ME at micromolar concentrations inhibits the migration of human vascular smooth muscle cells (Yin et al, ). The obtained data confirmed that 2‐ME may be considered as a physiological anticancer molecule (Gorska et al, ; Gorska, Kuban‐Jankowska et al, ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…42 Additionally, a myosin II inhibitor stabilized microtubules, 42 prompting investigators to look at the role of myosin II in MT regulation. They found that cells treated with MT destabilizing drugs exhibited an increase in rMLC phosphorylation, 43 while Taxol treatment abolished rMLC phosphorylation, 48 suggesting that MT organization is regulated through a Rho/ROCK/myosin II pathway. Our work shows that the sensitivity of MDA-MB-468 and MDA-MB-231 breast cancer cells to docetaxel-induced apoptosis is modulated through Rho and p190, possibly through the ROCK and rMLC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits smooth muscle contraction through endothelial NO release [181]. Yin et al demonstrated that cardioprotective effect of 2ME 2 is through the involvement of the integrindependent signalling, Ca 2+ mobilization, release of ROS, cAMP-PKA pathway and unspecified protein kinases/phosphatises in inhibiting atorvastatin induced human vascular smooth muscle cell rounding [182]. There are several other reports of inhibition of rat aortic smooth muscle contraction by 2ME 2 [183].…”
Section: Cardioprotective Activity Of 2mementioning
confidence: 95%